2020
DOI: 10.1136/bmjpo-2020-000858
|View full text |Cite
|
Sign up to set email alerts
|

Weaning strategies for the withdrawal of non-invasive respiratory support applying continuous positive airway pressure in preterm infants: a systematic review and meta-analysis

Abstract: BackgroundThe optimal method to wean preterm infants from non-invasive respiratory support (NIVRS) with nasal continuous positive airway pressure (CPAP) or high-flow nasal cannula is still unclear, and methods used vary considerably between neonatal units.ObjectivePerform a systematic review and meta-analysis to determine the most effective strategy for weaning preterm infants born before 37 weeks’ gestation from NIVRS.MethodEMBASE, MEDLINE, CINAHL, Google and Cochrane Central Register of Controlled Trials wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…When HFNC was used as a step-down for weaning from nCPAP, a significant reduction in postmenstrual age (PMA) at weaning was noted [mean difference (MD) –2.70 wk; 95% CI –8.37 to −1.52 wk]. However, there was a significantly longer duration of oxygen supplementation (MD 7.80 d; 95% CI 5.31–10.28 d) [ 7 ].…”
Section: What Is Noninvasive Ventilation (Niv)?mentioning
confidence: 99%
“…When HFNC was used as a step-down for weaning from nCPAP, a significant reduction in postmenstrual age (PMA) at weaning was noted [mean difference (MD) –2.70 wk; 95% CI –8.37 to −1.52 wk]. However, there was a significantly longer duration of oxygen supplementation (MD 7.80 d; 95% CI 5.31–10.28 d) [ 7 ].…”
Section: What Is Noninvasive Ventilation (Niv)?mentioning
confidence: 99%
“…A systematic review of nCPAP weaning indicated that this method of abrupt cessation significantly reduced the PMA of successful weaning. [34][35][36] For a non-inferiority weaning study with the…”
Section: Discussionmentioning
confidence: 99%
“…We did not use lower pressures or cycling. A systematic review of nCPAP weaning indicated that this method of abrupt cessation significantly reduced the PMA of successful weaning 34–36. For a non-inferiority weaning study with the primary outcome being time of respiratory support, we chose a weaning method that resulted in the shortest time on support.…”
Section: Discussionmentioning
confidence: 99%
“…However, this weaning process takes more time, and the final discontinuation of nCPAP comes at a later post-menstrual age. On the other hand, stepping down from nCPAP to HFNC shortens the duration of nCPAP treatment but is associated with a longer duration of oxygen administration [117].…”
Section: High-flow Nasal Cannulamentioning
confidence: 99%